2022
DOI: 10.1177/11206721221085870
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of anti-VEGF treatment of macular oedema due to retinal vein occlusions

Abstract: Purpose retinal vein occlusion (RVO) is classified as either branch (BRVO) or central (CRVO) RVO. The gold standard treatment for macular oedema (MO) secondary to RVO is intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections. Our study aimed to compare ranibizumab and aflibercept outcomes over a maximum follow-up of five years. Methods this retrospective study assessed treatment-naïve RVO patients. Active disease was treated with three loading injections followed by a pro-re-nata (PRN) reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…However, an important difference between the case of neovascular AMD and that of RVO is that there seems to be a continuing need for anti-VEGF therapy in eyes with neovascular AMD with a large proportion of patients remaining in active therapy for many years (Potapenko & la Cour, 2021); whereas for RVO, we find that only 52.1% of patients remains in active after the first year. Our findings are in line with other real-life studies of anti-VEGF therapy of RVO, which find that ~50% of patients remain in treatment after the first year (Corazza et al, 2022;Rezar et al, 2015). Furthermore, we also report that number of patients in active treatment decrease with 21.7% per following year; in other words, after 5 years <20% are expected to remain in active anti-VEGF therapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, an important difference between the case of neovascular AMD and that of RVO is that there seems to be a continuing need for anti-VEGF therapy in eyes with neovascular AMD with a large proportion of patients remaining in active therapy for many years (Potapenko & la Cour, 2021); whereas for RVO, we find that only 52.1% of patients remains in active after the first year. Our findings are in line with other real-life studies of anti-VEGF therapy of RVO, which find that ~50% of patients remain in treatment after the first year (Corazza et al, 2022;Rezar et al, 2015). Furthermore, we also report that number of patients in active treatment decrease with 21.7% per following year; in other words, after 5 years <20% are expected to remain in active anti-VEGF therapy.…”
Section: Discussionsupporting
confidence: 92%
“…It can be further speculated that introduction of new anti‐VEGF formulations or treatment may also influence treatment burden (Chakraborty et al, 2022; Dugel et al, 2020; Ghanchi et al, 2022; Heier et al, 2022). However, for RVO, studies on Aflibercept and Ranibizumab have so far not shown any clear differences in the number of injections beyond the first year (Corazza et al, 2022). Another important aspect is that willingness to adhere to regular anti‐VEGF treatments is lower in patients with neovascular AMD ≥ 90 years (Subhi & Sørensen, 2017), and a reasonable speculation is that an increasing number of patients with RVO in the very old category may exhibit similar difficulties in adherence to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, anti-VEGF drugs have been widely employed to treat fundus diseases such as nAMD, DME, and RVO, and have exhibited promising results. [9][10][11] Although it has been reported previously that intravitreal injection of anti-VEGF drugs might lead to complications such as vitreous hemorrhage, endophthalmitis and intraocular pressure increase, [12] there are few reports describing the possible influence of corneal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…In this real-world retrospective study, we found that anti-VEGF plus DEX I treatment improved BCVA, CRT, and retinal vessel density in patients with BRVO-ME and CRVO-ME, after an average of 3 injections. Previous studies have shown that intravitreal injection of anti-VEGF drugs (5.5 injections in 1 year) or DEX I can relieve RVO-ME [ 17 , 18 ]. Additionally, our findings indicated that after combination therapy RVO-ME patients had functional effects, and the curative effect peaked at 2 months after injection.…”
Section: Discussionmentioning
confidence: 99%